Lima festeja a la Inmaculada (1656): texto criollo y poderes urbanos - Latasa, Pilar (Pontificia Universidad Católica del Perú. Fondo Editorial, 2017)
Analysis of the festivities of the Immaculate Conception celebrated in Lima in 1656, from the account written by Diego de León Pinelo Gutiérrez. This Creole text reinterprets in baroque terms the cult of the Immaculate Conception in the City of Kings. Through it we can study these lengthy festivals, which involved the participation of the city’s most important institutions and corporate bodies, mobilizing considerable resources and people. Thus, the text is conceived as a political and religious exaltation of the city of Lima, typical of the festive genre and of the chorographic literature, which also connects with the emerging Creole discourse.

Este artículo analiza las fiestas a la Inmaculada que se celebraron en Lima en 1656 a partir de la relación festiva escrita por Diego de León Pinelo Gutiérrez. Este texto criollo reinterpreta en clave barroca la devoción inmaculista de la ciudad de Los Reyes. A través de él se estudian los prolongados festejos que contaron con la participación de las instituciones y corporaciones de poder más representativas de la ciudad y movilizaron considerables recursos y personas. Así, esta relación se concibe como una exaltación política y religiosa de la ciudad de Lima, propia del género festivo y de la literatura corográfica, que se conecta también con el naciente discurso criollo.
Keywords: Historia; https://purl.org/pe-repo/ocde/ford#6.01.01